The Effect of Plant Spacing and Number of Seeds per Planting Hole on the Growth and Yield of Sweet Corn (Zea mays saccharata Sturt) - Aisyah, Yuni; Mulyani, Cut; Adnan, Adnan (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Sweet corn productivity is strongly influenced by cultivation techniques, particularly plant spacing and the number of seeds per planting hole. This study aims to analyze the effects of plant spacing and the number of seeds per planting hole on the growth and yield of sweet corn (Zea mays saccharata Sturt). A quantitative approach was employed using a factorial Randomized Block Design with two treatment factors. The first factor was plant spacing, consisting of three levels: J1 = 50 cm × 25 cm, J2 = 60 cm × 25 cm, and J3 = 80 cm × 25 cm. The second factor was the number of seeds per planting hole, consisting of three levels: B1 = one seed, B2 = two seeds, and B3 = three seeds. The study was conducted from April to June 2025 at the Experimental Field of the Faculty of Agriculture, Universitas Samudra. Data were collected through direct observation and measurement of plant height, number of leaves, stem diameter, cob length, cob weight, cob weight without husk, and production per hectare. The data were analyzed using analysis of variance followed by the Least Significant Difference test. The findings indicate that plant spacing had a highly significant effect on plant height, cob length, cob weight, cob weight without husk per sample, cob weight without husk per plot, and production per hectare, but had no significant effect on the number of leaves and stem diameter. The best plant height was obtained from J3, whereas most yield parameters were best obtained from J2. The number of seeds per planting hole had a highly significant effect on all observed parameters, with B1 producing the best results. The interaction between plant spacing and number of seeds per planting hole significantly affected plant height at 30 and 45 days after planting and cob weight. The best plant height was obtained from J3B1, while the best cob weight was obtained from J2B1. This study concludes that the use of one seed per planting hole combined with appropriate plant spacing can improve sweet corn growth and yield. These findings provide practical implications for optimizing cultivation strategies to enhance sweet corn productivity.